CASE OF IDIOPATHIC UVEAL EFFUSION THAT DEVELOPED PROLIFERATIVE DIABETIC RETINOPATHY AFTER SCLERAL RESECTION SURGERY. Issue Volume 16:Issues 3(2022) (28th February 2020) - Baba, Takayuki; Yamamoto, Shuichi
Abstract : An eye with uveal effusion was treated by concurrent sclerectomies, but the uveal effusion recurred, and the pre-existing nonproliferative diabetic retinopathy rapidly progressed to proliferative diabetic retinopathy. Pars plana vitrectomy combined with cataract surgery successfully reattached the retina. Abstract : Background/Purpose: To report a diabetic patient with uveal effusion that developed proliferative diabetic retinopathy after unsuccessful scleral resection for the uveal effusion. Case Report: A 50-year-old Japanese man with nonproliferative diabetic retinopathy and uveal effusion in his right eye underwent partial thickness sclerectomies at the four quadrants to treat the uveal effusion. These procedures reduced the amount of subretinal fluid and thus the choroidal and retinal detachment. However, the retinal detachment recurred and proliferative diabetic retinopathy developed with pre- and subretinal proliferation at 5 months after the surgery. The patient then underwent pars plana vitrectomy combined with phacoemulsification and implantation of an intraocular lens. During the surgery, the vasoproliferative membrane was removed, panretinal photocoagulation was performed, and intraocular tamponade with silicone oil was performed. After the removal of the silicone oil, the retina remained attached but the visual acuity was 2/20 because of macular atrophy. Conclusion: Clinicians should be aware that treatment of a uveal effusion by scleral resection can lead to a progression of nonproliferative diabetic retinopathy to proliferative diabetic retinopathy.